Observation of enhanced dielectric coupling and room-temperature ferromagnetism in chemically synthesized BiFeO3@SiO2 core-shell particles - Shirolkar, Mandar M.; Das, Raja; Maity, Tuhin; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Physical Chemistry C, 2012)
We report the effect of SiO2 coating on the structural, magnetic, and dielectric properties of chemically synthesized high-purity BiFeO3 particles. The assynthesized BiFeO3 particles demonstrate properties comparable with those reported for bulk BiFeO3. On the other hand, the structural measurement on BiFeO3@SiO2 shows that the SiO2 coating has anisotropically compressed the lattice of BiFeO3 particles and stimulates the variation in the electron density. This affects magnetic and dielectric behavior of material. Frequency-dependent dielectric constant study at low temperature (20-325 K) revealed slight reduction (8-10%) in the dielectric constant of BiFeO3@SiO2 particles compared to uncoated BiFeO3 particles. The study reveals five anomalies at 234, 206, 146, 84, and 25 K located in close proximity to the linear magnetodielectric coupling and spin reorientation transitions. The loss tangent (approximate to 10(-3)) and alternating current (ac) conductivity (approximate to 10(-8) Omega(-1)cm(-1)) of BiFeO3@SiO2 particles are orders of magnitude lower than those observed for the BiFeO3 particles. The magnetic measurement shows the existence of room-temperature ferromagnetism in BiFeO3@SiO2 particles with average value of magnetic moment per Fe atom approximate to 0.030 mu(B) and appreciable coercivity as high as 120 Oe. The canted spin structure in the surface shell of BiFeO3@SiO2 particles show an enhanced magnetic property and shifted hysteresis loop. The magnetic measurement in close proximity to dielectric transitions revealed enhanced magnetization, suggesting the presence of anisotropies. It has been observed that SiO2 coating alters the properties of BiFeO3 particles. Our dielectric and magnetic measurements show enhanced coupling among the electric and magnetic ordered parameters in BiFeO3@SiO2 core-shell particles compared to uncoated BiFeO3 particles. The magnetic and dielectric properties of SiO2-coated BiFeO3 are similar to nanoparticles of BiFeO3 where interface plays a significant role.